HARDWARE - Payne, Frances; Lindsell, Marianne; Redback Publishing (Frenchs Forest, NSW : Redback Publishing, 2020)
What are all the parts of a computer called, and what do they all do? Find out the answers to these questions, and many more inside this book. An easy-to-understand guide that will have you sounding like an expert in no time! Computers are everywhere, from watches to satellites, and toys to vacuum cleaners. Just knowing how to switch computers on is no longer enough. Start your knowledge journey right here in this series for kids who want to be right at the leading edge as computers evolve into the future.
t What's inside the box? -- t Staying connected -- Tech terms for kids.
Includes index
Keywords: Computer input-output equipment -- Juvenile literature; Computers -- Juvenile literature; Computer input-output equipment